Effect of hyperglycemia on fertility in streptozotocin-induced diabetic male Wistar rats: focus on glucose transporters and oxidative stress (Medical Journal of Indonesia, 2021)
BACKGROUND Glucose transporters (GLUTs) and oxidant metabolism are associated with the mechanism of infertility. This study evaluated the impact of hyperglycemia on glucose and oxidant metabolisms of Sertoli cells (SCs). METHODS This study was an animal study to investigate the expression of messenger RNA monocarboxylate transporter 4 (MCT4), GLUT1, GLUT3, nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione peroxidase, catalase (CAT), and lactate dehydrogenase A (LDHA) of Wistar rats testes that were induced hyperglycemia. Reverse transcription polymerase chain reaction analysis was used. Hyperglycemic state in the Wistar rats was induced by streptozotocin. 24 rats were divided into 3 groups: non-hyperglycemia (control), 2-week, and 4-week hyperglycemic state. All data were collected and analyzed using SPSS version 15.0 (IBM Corp., USA). RESULTS The expression of glucose transporter (GLUT1 and GLUT3), lactate transporter (MCT4), and cellular defense protein against oxidant (Nrf2 and CAT) was significantly increased in the 2-week and 4-week hyperglycemic state groups with p<0.01, respectively. CONCLUSIONS Hyperglycemic state affects the metabolism of SCs. Alteration of GLUTs and oxidative metabolism may indicate metabolic alterations by a prolonged exposure to hyperglycemia that may be responsible for diabetes-related male infertility.